2021
DOI: 10.2217/imt-2020-0224
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibitors and Chemotherapy in First-Line NSCLC: a Meta-Analysis

Abstract: This study is a meta-analysis of randomized controlled trials involving first-line studies in which immune checkpoint inhibitors were added to chemotherapy and were compared with chemotherapy alone. The primary end point was overall survival (OS). The analyses used random-effects models and the Grading of Recommendations Assessment, Development, and Evaluation system to rate the quality of the evidence. Nine articles were included for qualitative and quantitative synthesis. A meta-analysis of the nine randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 31 publications
1
22
2
Order By: Relevance
“…Randomized controlled trials have confirmed that adding ICIs to chemotherapy can improve patient prognosis. 10 Mutations in proto-oncogenes and tumor suppressor genes probably affect the treatment response and survival of lung cancer patients. Exploring the genetic background of different populations is of great significance to predict lung cancer patients’ response to immunotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized controlled trials have confirmed that adding ICIs to chemotherapy can improve patient prognosis. 10 Mutations in proto-oncogenes and tumor suppressor genes probably affect the treatment response and survival of lung cancer patients. Exploring the genetic background of different populations is of great significance to predict lung cancer patients’ response to immunotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…During the last few years, cancer immunotherapy has demonstrated promising results with different types of tumors [9][10][11][12]. In particular, with the introduction of immune checkpoint inhibitor (ICI)-targeted immunotherapy, the immunotolerant tumor microenvironment can be overcome by reactivating T cells, enhancing anti-tumor immunity, and eliminating tumor cells more effectively [13].…”
Section: Introductionmentioning
confidence: 99%
“…The findings support the superiority of ICIs over docetaxel in pretreated NSCLC patients, and suggest that anti-PD-1 inhibitors may have a minor advantage over anti-PD-L1 inhibitors 2. Petrelli et al confirmed in their meta-analysis that there is moderate evidence that adding ICIs to chemotherapy improves overall survival (OS) when compared with chemotherapy alone 3. However, in a review of Zhu et al put forward different opinions.…”
Section: Introductionmentioning
confidence: 89%